2015
DOI: 10.1016/j.jbior.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Roles and regulation of neutral sphingomyelinase-2 in cellular and pathological processes

Abstract: Our understanding of the functions of ceramide signaling has advanced tremendously over the past decade. In this review, we focus on the roles and regulation of neutral sphingomyelinase 2 (nSMase2), an enzyme that generates the bioactive lipid ceramide through the hydrolysis of the membrane lipid sphingomyelin. A large body of work has now implicated nSMase2 in a diverse set of cellular functions, physiological processes, and disease pathologies. We discuss different aspects of this enzyme’s regulation from tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
170
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(175 citation statements)
references
References 153 publications
(178 reference statements)
4
170
0
1
Order By: Relevance
“…Sphingomyelinases are enzymes characterized by their pH dependency: acid, neutral, or alkaline. Sphingomyelinases catalyze the breakdown of sphingomyelin into phosphocholine and ceramide, often in response to environmental stress or inflammatory cytokine stimuli [2,3]. Nsm2 is a membrane-associated enzyme located in the inner leaflet of the plasma membrane and Golgi membranes; this enzyme releases ceramide in the cytoplasmic leaflet of cellular membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Sphingomyelinases are enzymes characterized by their pH dependency: acid, neutral, or alkaline. Sphingomyelinases catalyze the breakdown of sphingomyelin into phosphocholine and ceramide, often in response to environmental stress or inflammatory cytokine stimuli [2,3]. Nsm2 is a membrane-associated enzyme located in the inner leaflet of the plasma membrane and Golgi membranes; this enzyme releases ceramide in the cytoplasmic leaflet of cellular membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid generation of ceramide in response to extracellular stimuli is mediated by the activation of sphingomyelinases (SMases), which hydrolyze sphingomyelin (SM), a major component of cell membranes, into ceramide and phosphocholine (3,4). Three families of SMases (acid, neutral, and alkaline) have been identified that are classified by their pH optima, subcellular localization, protein fold, and function (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Three families of SMases (acid, neutral, and alkaline) have been identified that are classified by their pH optima, subcellular localization, protein fold, and function (5)(6)(7)(8). Neutral sphingomyelinase 2 (nSMase2, product of the SMPD3 gene) is the major neutral sphingomyelinase (N-SMase) in mammalian cells for the stressinduced generation of ceramide (4). TNF-α (9-15), cell confluence (16,17), oxidative stress (18)(19)(20), and inflammation (20,21) are all potent activators of nSMase2.…”
mentioning
confidence: 99%
“…phingomyelin phosphodiesterase 3 (SMPD3) is a lipid-metabolizing enzyme present in the membranes of the endoplasmic reticulum and the inner leaflet of the cell membrane (1). Recently, this enzyme has been identified to be a key regulator of skeletal development (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%